2022
DOI: 10.3390/ijerph19148860
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Awareness of the Risk of Exposure to Pollutants Occurring at Fire Scenes and Health Beliefs among Metropolitan Firefighters in the Republic of Korea

Abstract: Firefighters are repeatedly exposed to various pollutants that occur at fire scenes. There are three levels of exposure: primary exposure to pollutants, secondary exposure to pollutants on personal protective equipment (PPE), and tertiary exposure to contaminated fire stations and fire engines due to pollutants on PPE. Therefore, it is important for firefighters to be aware of the risk of exposure to pollutants and to practice health behaviors such as appropriate PPE management. No clear association has been e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…49 In contrast to findings by Oh about age influencing perceived cancer risk, age was not a factor in predicting decontamination behavior. 10 Bautista further found that peer-to-peer accountability was a strong facilitator, reinforcing the notion that the behavior of other firefighters is important to decontamination and risk reduction behaviors. 46 Aside from personal attitudes, beliefs, and norms, organizational factors can serve as facilitators for risk reduction.…”
Section: Facilitators To Risk Reduction Behaviorsmentioning
confidence: 70%
See 4 more Smart Citations
“…49 In contrast to findings by Oh about age influencing perceived cancer risk, age was not a factor in predicting decontamination behavior. 10 Bautista further found that peer-to-peer accountability was a strong facilitator, reinforcing the notion that the behavior of other firefighters is important to decontamination and risk reduction behaviors. 46 Aside from personal attitudes, beliefs, and norms, organizational factors can serve as facilitators for risk reduction.…”
Section: Facilitators To Risk Reduction Behaviorsmentioning
confidence: 70%
“…While some cancers (such as mesothelioma) have received considerable attention, today there is growing recognition of the dangers of multiple types of cancers among firefighters. Specifically, studies have found linkages between firefighting and numerous cancers, for example, bladder, 4,5,6 colorectal, 7,8 brain and central nervous system, 9,10 non-Hodgkin's lymphoma, 5,11,12 skin melanoma, 4,5,13 prostate and testicular, 5,13,14 with most having an increased mortality rate when compared to the general population. 4 Kidney cancer has also been found at increased rates, however, findings are less consistent for kidney cancer and certain other cancers, including Hodgkin's lymphoma, 2,11,12 leukemia, 4,15,16 lymphosarcoma and reticulosarcoma, 4 multiple myeloma, 4,17,18 and pancreatic cancer.…”
Section: Cancers and Rates Of Occurrencementioning
confidence: 99%
See 3 more Smart Citations